JNK Inhibition Inhibits Lateral Line Neuromast Hair Cell Development - Cai, Chengfu; Lin, Jinchao; Sun, Shaoyang; He, Yingzi (Frontiers in Cellular Neuroscience, 2016)
JNK signalling is known to play a role in regulating cell behaviours such as cell cycle progression, cell proliferation, and apoptosis, and recent studies have suggested important roles for JNK signalling in embryonic development. However, the precise function of JNK signalling in hair cell development remains poorly studied. In this study, we used the small molecule JNK inhibitor SP600125 to examine the effect of JNK signalling abrogation on the development of hair cells in the zebrafish lateral line neuromast. Our results showed that SP600125 reduced the numbers of both hair cells and supporting cells in neuromasts during larval development in a dose-dependent manner. Additionally, JNK inhibition strongly inhibited the proliferation of neuromast cells, which likely explains the decrease in the number of differentiated hair cells in inhibitor-treated larvae. Furthermore, western blot and in situ analysis showed that JNK inhibition induced cell cycle arrest through induction of p21 expression. We also showed that SP600125 induced cell death in developing neuromasts as measured by cleaved caspase-3 immunohistochemistry, and this was accompanied with an induction of p53 gene expression. Together these results indicate that JNK might be an important regulator in the development of hair cells in the lateral line in zebrafish by controlling both cell cycle progression and apoptosis.